Prevention of Solution Leakage during Polyacrylamide Gel Preparation - Jiang, Guijin; Zhao, Hanxiao; Liu, Hongxing; Lin, Ying; Shen, Yanlong; Yang, Xianyu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Polyacrylamide gel electrophoresis (PAGE) is an essential technique in molecular biology. However, solution leakage often leads to the failure of PAGE gel preparation. Here a simple method is reported to prevent the leakage for mini PAGE gel preparation by filling 400 μl of 1% hot agarose solution from the bottom of the assembled glass plates. This method makes almost no solution leakage during acrylamide polymerization ensuring the successful PAGE gel preparation and no bubbles trapped beneath the bottom of the gel having to be removed before the initiation of the electrophoresis.